A Critical Review of Social Exclusion and Inclusion among Immigrant and Refugee Women - J. Crawford; N. Kapisavanhu; J. Moore; C. Crawford; T. Lundy (Advances in Public Health)
International and global migration has risen over the last 50 years, and this trend is not expected to change. Immigrants and refugees make sociocultural and economic contributions to settlement states; however, this does not always mean that they feel included or welcomed. Social exclusion as a determinant of health reflects the social inequalities of some groups in a population over others. Immigrants and refugees are excluded from participating in social, economic, civic, and political domains within Western settlement countries; women experience greater social exclusion because of intersecting social identities and the interplay between sociostructural systems that create inequalities within host societies. To explore this phenomenon more fully, we conducted a critical review of how social exclusion and inclusion are experienced by women settling in Western contexts and the factors that impact daily life and health. Intersectionality was the lens with which we situated, examined, and analyzed the findings of the critical review to inform the development of a conceptual model. A five-stage process was used to comprehensively review the literature using six databases. Sixty papers were included in the review. The conceptual model highlighted two overarching themes that were further distinguished by micro-, meso-, and macro-level factors of exclusion and inclusion. The first theme considers the causes and outcomes of social exclusion represented as social determinants in the context of settlement and includes social environment, social supports, language ability, discrimination and racism, settlement and identity, income and employment, education and professional credentials, institutions, and government services. The second theme of social inclusionary processes consisted of social capital, social and civic participation, empowerment, and policies and settlement programs. The conceptual model advances knowledge of potential improvements required in formal settlement programs and the importance of informal programs that collectively may enhance inclusion for immigrant/refugee women and their families in Western contexts.